THE IMPLEMENTATION OF AUDIO LINGUAL METHOD IN TEACHING VOCABULARY USING SONG TO THE FIFTH YEAR STUDENT OF SD N 03 KEBAK - INDRAWATI, NURUL AGUSTINA (2011)
This qualitative research aims at describing the result of the implementation in teaching vocabulary using audio lingual method by song at the fifth year students of SD N 03 Kebak. It is conducted to describe the process of teaching-learning vocabulary using audio lingual method, the method used in teaching vocabulary, the classroom activity, the result of the implementation in teaching vocabulary using audio lingual method by song, and the problems faced by the teacher when they were teaching English vocabulary using audio Lingual Method by song. The writer gets the data of this research from field note, observation, and interview. The techniques of collecting data are the observation, interview and document. The data are information relating to the implementation of audio lingual method in teaching vocabulary using song and problems faced by the teacher at SD N 03 Kebak. The result of the analysis shows that the goals of teaching vocabulary are helpful for the students to make easier in learning vocabulary. The teacher uses target language to convey the material and make the students easy to memorize the vocabulary. The students feel happy, they can be more active, and enjoy the English. They can pronounce, spell, and memorize the English words well. The conclusion is teaching vocabulary using audio lingual method at SD N 03 Kebak is good and effective. The teacher faces several problems in teaching vocabulary, namely: class management, motivation of the students, and vocabulary ability.